(untitled) (Development Service Industry Management, 2024)
Radical transformations in the domestic health care system, caused by significant challenges and threats to both the domestic health care system, citizens of Ukraine, and national security, actualize the need to review approaches to the management of medical institutions in Ukraine. In modern conditions, the transformation of their economic status (acquiring the characteristics of an economic agent) and the corresponding change in the management paradigm and management decision-making tools should be considered among the primary tasks of reforming the management process of health care institutions. A certain reflection on the mentioned changes should be the introduction of new approaches to the management of economic systems of medical institutions, which are typical for participants in market relations. The purpose of the study is the analysis of the modern economic environment of the functioning of medical institutions, the study of factors that negatively affect their safety, as well as the formation of the components of the mechanism of safety-oriented management of health care institutions. The functioning of the existing "traditional" organizational and economic model of health care institutions led to the accumulation of systemic problems and did not make it possible to effectively ensure citizens’ access to high-quality and affordable medical care. In addition, the organizational and economic parameters of their work did not create prerequisites for the development of health care institutions in the context of their achievement of the relevant infrastructural, personal and professional indicators. The main difference between the "traditional" organizational and economic model and the "patient-oriented" one is the purpose of existence, namely the activity of the "traditional" model involves the performance of certain social functions without orientation to the result. The introduction of the principles of the "patient-oriented" economic and organizational model of health care institutions is focused on a comprehensive result, which includes the provision of quality medical services with the most effective use of the resources of the health care institution, which will allow the formation of an appropriate management system aimed at development. The economic space for the functioning of medical institutions increasingly corresponds to the conditions of market relations, which are characterized by competition, market pressure, ensuring the safety of patients and health care institutions, the importance of achieving a high level of quality of medical services, and dependence on providers and consumers of medical services. The transformation of these approaches actualizes the need to develop a new internal economic mechanism for the functioning of medical institutions, the parameters and requirements of which are determined under the influence of a certain set of internal and external factors. The introduction of a new internal economic mechanism of health care institutions actualizes the need to use safety-oriented management approaches, which should be understood as a set of effective measures aimed at increasing the effectiveness of the management system’s response processes to existing internal and external threats, which involves finding a sufficient amount of resources (financial, personnel , material and technical) to neutralize the specified threats in order to find a balance between development priorities and priorities for ensuring the safety of health care facilities. Safety-oriented management is of crucial importance in terms of ensuring the sustainability of the provision of medical services, the sufficiency of material, personnel and financial resources and the availability of quality medical care. The goals of safety-oriented management are provided by the components of the economic security system of health care facilities, namely: protection of medical facilities from external and internal threats; ensuring stable economic growth, infrastructural development, increasing indicators and ensuring the stability of the functioning of institutions in crisis situations (economic downturns, pandemics and natural disasters).